2010
DOI: 10.1007/s10853-010-4683-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica nanoparticles on compressive properties of an epoxy polymer

Abstract: The effect of nanosilica on compressive properties of an Epikote 828 epoxy at room temperature was studied. A 40 wt% nanosilica/epoxy masterbatch (nanopox F400) was used to prepare a series of epoxy based nanocomposites with 5-25 wt% nanosilica content. Static uniaxial compression tests were conducted on cubic and cylindrical specimens to study the compressive stress-strain response, failure mechanisms and damage characteristics of the pure and nanomodified epoxy. It was found that the compressive stiffness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 31 publications
(39 reference statements)
2
69
0
Order By: Relevance
“…Hodzic et al 42 used benzyldimethylamine as an accelerator for an anhydride curing agent in their study of static uniaxial compression. In contrast to that of classic micrometer-sized fillers, the addition of nanoparticles enhanced the compressive stress-strain behavior of the cured epoxy resin.…”
Section: Anhydride-cured Epoxy Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hodzic et al 42 used benzyldimethylamine as an accelerator for an anhydride curing agent in their study of static uniaxial compression. In contrast to that of classic micrometer-sized fillers, the addition of nanoparticles enhanced the compressive stress-strain behavior of the cured epoxy resin.…”
Section: Anhydride-cured Epoxy Resinsmentioning
confidence: 99%
“…In another study, Hodzic et al 43 employed both cylindric and prismatic test specimens. In both cases, the test specimen with the highest addition level of nanosilica showed the best performance.…”
Section: Anhydride-cured Epoxy Resinsmentioning
confidence: 99%
“…On the other hand, when the interfacial adhesion is high the agreement between the predictions and the experimental data is more comparable. It should be noted that these three models have been used previously to predict the moduli of silica nanoparticle in epoxy polymers 18 . This study found that at concentrations of nanosilica such as at 20%wt the Lewis-Nielsen 'slip' model gave the best agreement with the measured values.…”
Section: Comparison Of Experimental and Predicted Elastic Modulusmentioning
confidence: 99%
“…Fractography using SEM indicated that, on a micrometre scale the nanoparticle-induced dimples were the major toughening mechanism causing energy dissipation. Jumahat et al 18 studied the static uniaxial compression tests of cubic and cylindrical specimens in order to study the compressive stress-strain response, the failure mechanisms and damage characteristics of the pure and nanomodified with silica epoxy. It was found that the compressive stiffness and strength were improved with increasing nanosilica content without significant reduction in failure strain.…”
Section: Introductionmentioning
confidence: 99%
“…So far the improvement in properties of composites with silica has always resulted from high concentrations of the latter [32][33][34]. Jumahat et al [35,36] reported the addition of 13 wt% nanosilica into epoxy matrix enhanced the compressive modulus by 19% and compressive strength by The high percentages of silica significantly increase the viscosity of compositions and influence many intrinsic properties of epoxy matrix and further, processability of the resin. Therefore, development of an effective, convenient, and low-cost process toward high performance silica modified epoxy based hybrid composites with uniform dispersion of nanosilica and better silica-epoxy adhesion warrant more research.…”
Section: Mechanical Properties Of Compositesmentioning
confidence: 99%